1995
DOI: 10.1021/bi00015a031
|View full text |Cite
|
Sign up to set email alerts
|

Autophosphorylation of Smooth Muscle Myosin Light Chain Kinase at Its Regulatory Domain

Abstract: Autophosphorylation of smooth muscle myosin light chain kinase was initially reported by Foyt et al. [Foyt, H. L., & Means, A. R. (1985) J. Cyclic Nucleotide Protein Phosphorylation Res. 260, 8978-8983], however, the effects of autophosphorylation on the kinase activity as well as the location of the sites have not been elucidated. Here we demonstrate that MLCK is autophosphorylated at three sites, Thr 803, Ser 815, and Ser 823, and this phosphorylation alters MLCK activity. Two phosphorylation sites are locat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
31
0

Year Published

1996
1996
2003
2003

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(37 citation statements)
references
References 43 publications
6
31
0
Order By: Relevance
“…The 32 P incorporation into MLCK-1 was essentially abolished by the specific p60 src kinase inhibitor PP-2 (250 nM). However, all three MLCK isoforms exhibited low level of 32 P incorporation even in the absence of p60 src (0.63 Ϯ 0.21 mol of PO 4 /mol of protein) consistent with the MLCK autophosphorylation previously described for smooth muscle MLCK (39,40). This was confirmed by heat treatment of the MLCK preparations (70°C for 5 min), which completely abolished incorporation of 32 P into MLCK in the absence of p60 src (data not shown).…”
Section: In Vitro Phosphorylation Of Mlck Isoforms By P60supporting
confidence: 83%
See 2 more Smart Citations
“…The 32 P incorporation into MLCK-1 was essentially abolished by the specific p60 src kinase inhibitor PP-2 (250 nM). However, all three MLCK isoforms exhibited low level of 32 P incorporation even in the absence of p60 src (0.63 Ϯ 0.21 mol of PO 4 /mol of protein) consistent with the MLCK autophosphorylation previously described for smooth muscle MLCK (39,40). This was confirmed by heat treatment of the MLCK preparations (70°C for 5 min), which completely abolished incorporation of 32 P into MLCK in the absence of p60 src (data not shown).…”
Section: In Vitro Phosphorylation Of Mlck Isoforms By P60supporting
confidence: 83%
“…Finally, mass spectrometry analysis of the fragments obtained after cyanogen bromide cleavage of the MLCK-1 suggested that the two phosphate groups are contained within the Lys 1721 -Met 1761 EC MLCK fragment (data not shown) consistent with the presence of the EC MLCK-1 autophosphorylation sites Thr 1748 and Ser 1760 , which are homologous to the previously described SM MLCK autophosphorylation sites Thr 803 and Ser 815 (39).…”
Section: Identification Of P60supporting
confidence: 66%
See 1 more Smart Citation
“…It is known that calmodulin-dependent protein kinase II is significantly activated by autophosphorylation at Thr 287 , which lies near the autoinhibitory region of the kinase (53)(54)(55). The autophosphorylation-induced activation of the protein kinase activity is also known for myosin light chain kinase, in which the autophosphorylation site is found to be in close proximity to the autoinhibitory region (56). Because autophosphorylation is the intramolecular process, the rate of autophosphorylation is independent to myosin III concentration, and therefore the observed rate in the present study probably represents the rate in the cell environment.…”
Section: Discussionmentioning
confidence: 99%
“…Wehave shown that mitotic Hela cell extracts have higher smMLCK kinase activities than nonmitotic cell extracts (1 1). This mitosis-specific kinase activity is thought to be cdc2 ki- Furthermore, autophosphorylation of smMLCK has been reported (6,7,23 pmol) in a final volume of 140 fA. Twenty fA of aliquots were withdrawn at the indicated times and mixed with 5 x SDSsample buffer to stop the reactions.…”
mentioning
confidence: 99%